2019
DOI: 10.15832/ankutbd.424218
|View full text |Cite
|
Sign up to set email alerts
|

Growing Degree Day and Seed Yield Relationships in Mustard (Brassica juncea L.) Under Different Sowing Seasons and Locations of Turkey

Abstract: Mustard is grown in mild winter regions as late fall and in hard winter regions as late spring crop. Mustard has high degree of adaptability under wide range of climatic conditions in Turkey. Temperature is an important weather parameter affecting the growth and development of the mustard. The sum growing degree day (GDD) for a growing season is related to plant development which is depends on the accumulation of heat. The aim of this study was to determine the adaptation of mustard, under sowing seasons (spri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…Acording to mean locations, the maximum crude oil content (29.1%) was determined for A2 genotype. The results emphasize that these differences between locations might be due to environmental factors like soil structure, air temperature and precipitation (Shafii et al, 1992;Kayacetin et al, 2019). The results suggest potential of these genotypes for use in future breeding programs and supported the findings of Getinet et al, (1997); Ashraf et al, (1999).…”
Section: Resultssupporting
confidence: 81%
“…Acording to mean locations, the maximum crude oil content (29.1%) was determined for A2 genotype. The results emphasize that these differences between locations might be due to environmental factors like soil structure, air temperature and precipitation (Shafii et al, 1992;Kayacetin et al, 2019). The results suggest potential of these genotypes for use in future breeding programs and supported the findings of Getinet et al, (1997); Ashraf et al, (1999).…”
Section: Resultssupporting
confidence: 81%
“…From this result, the SWC lower limit in this experiment was set at the level of 20%, and this seems in line with what other researchers had concluded based on their experimental SWC conditions. Researchers reported a volumetric water content between about 0.1 and 0.16 cm 3 /cm 3 (10% and 16% SWC), which produced the most favourable yield for growing spinach in Tottori, Japan [20]. Other researchers set soil moisture deficit conditions at 7.5%, 17.5%, 25%, 30%, and 35% for growing microgreens and found that 17.5% can provide an optimal yield [21].…”
Section: Methodsmentioning
confidence: 99%
“…Fall season crop in Aydın location had the maximum growing degree-days. Overall, fall season accumulated more growing degree-days due to longer period of sunshine in comparison to spring season with less sunshine days and longer vegetation period (Kayacetin et al, 2019). The seeds of these species could be harvested upon achieving ~8.5% moisture content at maturity (CFIA, 1999).…”
Section: Possibilities Of Mustard Cultivation In Turkeymentioning
confidence: 99%